The interplay between oxidative stress and autophagy: focus on the development of neurological diseases - Talebi, Marjan; Mohammadi Vadoud, Seyyed Ali; Haratian, Alireza; Talebi, Mohsen; Farkhondeh, Tahereh; Pourbagher-Shahri, Ali Mohammad; Samarghandian, Saeed (Behavioral and brain functions, 2022)
Regarding the epidemiological studies, neurological dysfunctions caused by cerebral ischemia or neurodegenerative diseases (NDDs) have been considered a pointed matter. Mount-up shreds of evidence support that both autophagy and reactive oxygen species (ROS) are involved in the commencement and progression of neurological diseases. Remarkably, oxidative stress prompted by an increase of ROS threatens cerebral integrity and improves the severity of other pathogenic agents such as mitochondrial damage in neuronal disturbances. Autophagy is anticipated as a cellular defending mode to combat cytotoxic substances and damage. The recent document proposes that the interrelation of autophagy and ROS creates a crucial function in controlling neuronal homeostasis. This review aims to overview the cross-talk among autophagy and oxidative stress and its molecular mechanisms in various neurological diseases to prepare new perceptions into a new treatment for neurological disorders. Furthermore, natural/synthetic agents entailed in modulation/regulation of this ambitious cross-talk are described.